Long-term power consumption demand prediction: a comparison of energy associated and bayesian modeling approach - Rodriguez Rivero, Cristian (2015)
Fil: Rodriguez Rivero, Cristian. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales. Departamento de Ingeniería Electrónica; Argentina.